Sarcoptic mange in guanacos: transmission to sheep and goats and treatment with moxidectin - PAPADOPOULOS (Η. ΠΑΠΑΔΟΠΟΥΛΟΣ), E.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ), G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Two guanacos were diagnosed with sarcoptic mange, confirmed by recovery of mites, using standard parasitological techniques, from skin scrapings. Each animal was treated twice, 10 days apart, with moxidectin 1% inj. sol. administered subcutaneously. Dose rate was 0.2 mg/kg bodyweight. After the injections, safety observations were made for local or general adverse reactions. Moreover, clinical examinations were made and skin scrapings were collected and examined. After treatment, neither changes were seen at the site of injection, nor general reactions were recorded. The mange skin lesions had disappeared by 42nd day post treatment. No mites were recovered 21 d post-treatment. Thereafter, sheep and goats neighbouring the guanacos developed sarcoptic mange, confirmed by clinical findings and recovery of mites. In contrast, horses, donkeys and dogs, also neighbouring the guanacos, did not develop sarcoptic mange. It is concluded that moxidectin can be used for the treatment of sarcoptic mange in guanacos. The findings support a hypothesis that mites may be transmitted easily among ruminants; these are in line with results of in vitro studies, indicating that mite strains from ruminants belong to the same cluster.